Plasma 25-hydroxyvitamin D and colorectal cancer risk according to tumour immunity status. Issue 2 (15th January 2015) - Song, Mingyang; Nishihara, Reiko; Wang, Molin; Chan, Andrew T; Qian, Zhi Rong; Inamura, Kentaro; Zhang, Xuehong; Ng, Kimmie; Kim, Sun A; Mima, Kosuke; Sukawa, Yasutaka; Nosho, Katsuhiko; et al.
Abstract : Objective: Evidence suggests protective effects of vitamin D and antitumour immunity on colorectal cancer risk. Immune cells in tumour microenvironment can convert 25-hydroxyvitamin D [25(OH)D] to bioactive 1α, 25-dihydroxyvitamin D3, which influences neoplastic and immune cells as an autocrine and paracrine factor. Thus, we hypothesised that the inverse association between vitamin D and colorectal cancer risk might be stronger for cancers with high-level immune response than those with low-level immune response. Design: We designed a nested case–control study (318 rectal and colon carcinoma cases and 624 matched controls) within the Nurses' Health Study and Health Professionals Follow-up Study using molecular pathological epidemiology database. Multivariable conditional logistic regression was used to assess the association of plasma 25(OH)D with tumour subtypes according to the degree of lymphocytic reaction, tumour-infiltrating T cells (CD3+, CD8+, CD45RO+ (PTPRC) and FOXP3+ cells), microsatellite instability or CpG island methylator phenotype. Results: The association of plasma 25(OH)D with colorectal carcinoma differed by the degree of intratumoural periglandular reaction (p for heterogeneity=0.001); high 25(OH)D was associated with lower risk of tumour with high-level reaction (comparing the highest versus lowest tertile: OR 0.10; 95% CI 0.03 to 0.35; p for trend<0.001), but not risk of tumour with lower-level reaction (p for trend>0.50). A statistically non-significant difference was observed for the associations of 25(OH)D with tumour subtypes according to CD3+ T cell density (p for heterogeneity=0.03; adjusted statistical significance level of α=0.006). Conclusions: High plasma 25(OH)D level is associated with lower risk of colorectal cancer with intense immune reaction, supporting a role of vitamin D in cancer immunoprevention through tumour–host interaction.